THE CPA AND MANAGEMENT SERVICES. - Patrick, A. W.; Quittmeyer, C. L. (The Accounting Review, 1963)
This article focuses on the role of certified public accountants (CPA) in management services. Demands on businesses have multiplied over the years as a result of the changing nature of competitive markets, rapid developments in technology of production equipment, availability and increased use of high-speed computers, expansion of knowledge in almost every field of learning, and a constant increase in the number, variety, and complexity of laws affecting business operations. Yet, in spite of all the encouragement given by professional organizations, the cries of business managers for more help and the cold statistics on the volume and lucrative rewards of the consulting business, many CPA have apparently not entered this field nor are they relatively frequently called upon by firms seeking consulting services. Some CPA firms are very active in rendering management services, but the number of firms who are is quite small. Further- more, revenue received by a CPA for management services is a very small portion of the total annual fees of $550 million paid by businesses for consulting work, as well as a small percentage of the total revenues realized by a CPA.